Career Progression as Predictor on Job Satisfaction of Academic Librarians in the Bicol Region, Philippines - Ester Listor (JPAIR Institutional Research Journal)
Career progression is an employee’s professional development that provides security, satisfaction, and a sense of professional fulfillment. This study determines the effect of career progression as a predictor of job satisfaction for academic librarians in the Bicol Region. Specifically, this aims to determine the respondent’s personal, professional, and employment profile; level of job satisfaction in terms of career progression, work motivation, working environment, fair compensation, job security, and administrative support; the significant difference in the level of job satisfaction and the perceived challenges and opportunities encountered as they progress in their career. This study utilizes a convergent parallel mixed method with 113 respondents, comprising 63 from private HEIs and 50 from public libraries, including SUCs and LUCs. Findings revealed that school administrators gave career progression due importance. Good working environment was provided; however, the compensation package is not that attractive compared to Public HEIs. Lack of administrative support was observed; hence, it was recommended that School Administrators, would show commitment towards the improvement/advancement of libraries through enough funding. Librarians may also seek sponsorship/scholarships to improve their education and training. However, well-planned policies and conditions for these benefits could be articulated in the personnel and library administrative manual. Likewise, Human Resource Managers may consider calibrating the compensation and benefits of librarians to be at par with the faculty in compliance with the equivalency of librarians to teachers.